Mini review on Halal Food Colorants and Potential Sources - Wan Sulaiman, Wan Syibrah Hanisah; Md Zaini, Haslin Hanani; Othman, Rashidi (Halalsphere, 2023)
According to Qur’an, every Muslim must ensure that their food comes from Halal sources. In addition, being taught to be conscious that food and goods must be Halal, Muslims must also be cognizant of the quality. The rest of the world is gradually beginning to see the significance of the Muslim need for Halal food and other consumables. For example, Malaysia, a diverse Muslim country, has a broad selection of Halal products and services and a high standard for food quality. As a result of the expansion of the food industry, societies now have access to a wide range of food products, including common foods, confections, desserts, and snacks. Despite the recent reduction in the permissible amount of synthetic colourants for consumer health reasons, many distinct synthetic food dyes continue to be widely utilised due to their low cost, high efficiency, and outstanding stability. Industry and customer awareness of Halal food and its quality should be evident. Hence, this paper aims to understand the issue and Halal concept in food. Focusing on food colourants sources and acknowledging the Halal standard in Malaysia. Based on the finding from this study, the concept of Halal should be combined with safety and health for consumer health, and there is a need for research into new resources for Halal colourants, particularly from natural colourant pigments compared to synthetic colourants.